A study on the Knowledge of Accreditation Standards of Medication Management among Health Care Workers in a Tertiary Care Hospital. - Rejili Grace Joy Manickaraj, Krishnan V, Sindhura Myneni, Divya Ravikumar, Poonguzhali Sivagananam, Sumetha Suga, Sai Ravi Teja Kamineni, Kavin Mozhi James, Vahithamala Kunasekaran, Mythili Krishnan, Vishnu Priya V, Surapaneni Krishna Mohan (International Journal of Advanced Science and Technology, 2020)
Background:Medication management is that optimizes safe, effective, appropriate drug therapy for patient’s care. This study was conducted to assess the knowledge of accreditation standards of Medication Management among health care workers. Materials & Methods: A cross-sectional study was conducted among healthcare workers working in tertiary care hospitals across Chennai Tamil Nadu. A total of 370 were responded.A semi structured questionnaire was developed to explore the knowledge of accreditation standards of medication management among healthcare workers. Data was collected and analysed. Results: Out of 370 responders, majority(82.7%) of them were females. Majority (56.2%) were between the age group of 21-25 years. 87.6% were Nursing, 6.2% belongs to Allied Health Sciences, 4.3% were Pharmacists, 1.1% belong to medicine and 0.8% were Dentists. Majority(80.3%) of the respondents had previous knowledge on medication management. 77.8 % had adequate knowledge, 21.6% had moderate knowledge and 0.5% had inadequate knowledge on medication management. The average mean knowledge of the study participants was 30.00±4.031. Association between knowledge of medication management with demographic variables were statistically significant. Conclusion: The present study shows majority of health care workers had adequate knowledge on Medication Management. Continuous monitoring and Audits are to be conducted periodically in every stage regarding medication management to reduce the incidence of medication errors. More importance should be put into the basic nursing education to improve the nurses knowledge on medication management to reduce the risk of errors.